1998
DOI: 10.1108/01437739810234341
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of perceived leadership style in a culturally mixed environment

Abstract: Darwish A. Yousef Correlates of perceived leadership style in a culturally mixed environment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…7, No. 11;2014 commitment was significant and positive relationship (Yousef, 1998;Chen & Francesco, 2000;Lok & Crawford 2001;Xenikou & Simosi, 2006;Rad & Yarmohammadian, 2006, Hu, et al, 2009Shurbagi & Zahari, 2012b).…”
Section: Determinants Of Job Satisfactionmentioning
confidence: 94%
“…7, No. 11;2014 commitment was significant and positive relationship (Yousef, 1998;Chen & Francesco, 2000;Lok & Crawford 2001;Xenikou & Simosi, 2006;Rad & Yarmohammadian, 2006, Hu, et al, 2009Shurbagi & Zahari, 2012b).…”
Section: Determinants Of Job Satisfactionmentioning
confidence: 94%
“…Specific characteristics and qualifications of international executives influence their multicultural management style. Yousef (1998) found that there are significant relationships between the leader's personal characteristics such as age, education, gender, national culture, experience and performance. These characteristics of the leader should influence the multicultural management style.…”
Section: Conceptual Model Of Organizational Effectiveness and Leadershipmentioning
confidence: 99%
“…An organization that is short of capital may resort to borrowing money, and one in a poor location has the option to move. However an organization with short of leadership has little chance for survival (Yousef, 1998).…”
Section: Introductionmentioning
confidence: 99%